The Role of Active Social Loafing and Psychological Encouragement in Human Capital Development - Daryono Daryono; Christopher Foertsch (Jurnal Manajemen Bisnis, 2023)
Research aims: The general purpose of this study is to look at previous research on individual performance and several factors that can effect it, such as psychological encouragement and social loafing.Design/Methodology/Approach: Surveys were used to collect data for this type of quantitative study. The census method was employed in this study, with 124 respondents from the Instructors Department of Central Java National Police School representing 100% of the population. Simple regression analysis was utilized to determine the influence of independent and dependent variables.Research findings: Active social loafing negatively and significantly influenced instructor’s individual performance at a National Police School, while psychological encouragement positively and significantly influenced the instructors’ individual performance. In addition, psychological encouragement moderated the influence of social loafing on the Instructor's Department of the Central Java National Police School, representing individual performance.Theoretical Contribution/Originality: This literature can be used as a recommendation and additional information concerning management practices at the Central Java National Police School, in which social loafing has mainly occured.Practitioners/Policy Implications: This observation’s data and findings can be a reference point for for future social, psychological, and individual development research.Research Limitations/Implications: Demographic factors might affect an individual's performance and were not used in this research as control variables.